Conifer Seedling Survival in Response to High Surface Temperature Events of Varying Intensity and Duration - Rank, Robin; Maneta, Marco; Higuera, Philip; Holden, Zachary; Dobrowski, Solomon (Frontiers in Forests and Global Change, 2022)
Forests face accelerating threats due to increases in the severity and frequency of drought and heat stress associated with climate change. In particular, changing patterns of forest regeneration after disturbance will be important in predicting future forest distribution across the western United States, where patterns of recurring fire and regrowth are important in establishing landscape dynamics. To predict shifting landscape patterns, it will be important to identify environmental boundaries for forest regeneration using environmental variables with clear consequences for seedling survival. Here we explore soil surface temperature as an environmental variable with direct consequences for seedling survival and forest regeneration potential. We conducted a literature search to identify five previous laboratory experiments, spanning a period of 1924 to 1986, that exposed conifer seedlings to elevated soil surface temperatures for varying durations. We then synthesized the data from these studies to explore the survival of western U.S. conifer species in response to to differing surface temperature levels. We found mortality thresholds consistent with previously reported measurements in field and lab studies, but found that as surface temperatures reach these lethal thresholds the duration of exposure matters greatly to survival outcomes. This work leverages an intuitive climate metric with clear consequences for seedling survival as an indicator of forest regeneration potential.